Inhibition of Mef2a Enhances Neovascularization via Post-transcriptional Regulation of 14q32 MicroRNAs miR-329 and miR-494 - Sabine M.J. Welten; Margreet R. de Vries; Erna A.B. Peters; Sudhir Agrawal; Paul H.A. Quax; A. Yaël Nossent (Elsevier, 2017)
Improving the efficacy of neovascularization is a promising strategy to restore perfusion of ischemic tissues in patients with peripheral arterial disease. The 14q32 microRNA cluster is highly involved in neovascularization. The Mef2a transcription factor has been shown to induce transcription of the microRNAs within this cluster. We inhibited expression of Mef2a using gene-silencing oligonucleotides (GSOs) in an in vivo hind limb ischemia model. Treatment with GSO-Mef2a clearly improved blood flow recovery within 3 days (44% recovery versus 25% recovery in control) and persisted until 14 days after ischemia induction (80% recovery versus 60% recovery in control). Animals treated with GSO-Mef2a showed increased arteriogenesis and angiogenesis in the relevant muscle tissues. Inhibition of Mef2a decreased expression of 14q32 microRNAs miR-329 (p = 0.026) and miR-494 (trend, p = 0.06), but not of other 14q32 microRNAs, nor of 14q32 microRNA precursors. Because Mef2a did not influence 14q32 microRNA transcription, we hypothesized it functions as an RNA-binding protein that influences processing of 14q32 microRNA miR-329 and miR-494. Mef2A immunoprecipitation followed by RNA isolation and rt/qPCR confirmed direct binding of MEF2A to pri-miR-494, supporting this hypothesis. Our study demonstrates a novel function for Mef2a in post-ischemic neovascularization via post-transcriptional regulation of 14q32 microRNAs miR-329 and miR-494.